IDENTIFICATION OF POTENTIAL REGION IN WEST BANDUNG DISTRICT AS GEOPARK REGION - Mulyadi, Asep; Renata, Windya; Ruhimat, Mamat (Jurnal Pendidikan Geografi Gea, 2018)
The aims of this research are: (1) To identify geographical condition in West Bandung regency related to geopark development (2) To analyze Geopark condition Based on Geo-diversity, Bio-diversity and Cultural-diversity. (3) Identify the various efforts that can be done for the development of Geopark area in West Bandung regency. This research is descriptive research with survey method. The results showed that the geographical conditions are very diverse, there are various formations covered by various variations of rocks. Ikim belongs to the middle classification. The results of research have 15 locations that have potential to become Geopark Area. Sturges calculation shows that West Bandung regency worthy to be made Geopark Area. Scoring results on variables expressed by the Global Geopark Network is still somewhat less so that requires management to make West Bandung District as a Geopark Area.Keywords: bio-diversity, cultural-diversity, geodiversity, geopark